The Influence of Excellent Library Service and Communication on Students’ Reading Interests - Kurniawan, Edwar Fajri; Pahlawan, Pahlawan; Kristiawan, Muhammad (PPSDP International Journal of Education, 2025)
This study aims to determine and analyze (1) the influence of excellent library service on students’ reading interest; (2) the influence of communication on students’ reading interest; (3) the influence of excellent library service and communication together on students’ reading interest. This study is a quantitative study with a correlation method. This study was conducted at SMA Negeri 3 Tanah Abang with 68 students as respondents. The data collection technique used a questionnaire. The validity test used the product moment formula, while the reliability test used Cronbach’s alpha. The analysis prerequisite test used the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, correlation test, and the data was analyzed using multiple regression analysis techniques. The results of the study showed that (1) there was an influence between excellent library service and students’ reading interest of 74.3%; (2) there was an influence between communication on students’ reading interest of 76.1%; (3) There was an influence between excellent library service and communication on students’ reading interest of 79.9%. This research shows that library and Communication services have a significant effect on students’ reading interest. supporting the strengthening of literacy culture. These findings are useful for librarians, educators, and policymakers to improve literacy through effective services and communication.